Some Features of the Semantic Field of "Horse Gaits" in Mongolian Language - Gombo, Gerelmaa (Mongolian Language and Literature Studies, 2025)
While there are relatively few terms related to horse gaits in the hippology study, words with such characteristics are relatively abundant in the structure of Mongolian folk riddles and proverbs. This is partly because the nomadic economy that Mongolians have been engaged in since ancient times involves constant interaction with livestock, which are living objects with their own unique behaviors, emotions, and temperaments. The appearance and physical characteristics of these animals change according to seasonal and climatic conditions，so it requires to be keen on observational skills to manage and care for their livestock from nomads. Therefore, nomads develop the ability to distinguish their own hundreds of livestock from one another, as well as from those of other families, by identifying and naming their unique characteristics, such as color, age, sex, behavior, and movement patterns. Thus, the Mongolian language has been developed with a extensive and nuanced vocabulary related to livestock, reflecting the importance of animal husbandry in Mongolian culture and daily life. By observing the structure of folk proverbs and riddles alone, we can see that Mongolians have categorized the basic movements of horses into 11 general categories, and within those categories, they have distinguished and described over 50 different variations, creating a semantic field that names and describes horse movements. Монгол хэлэнд "адууны явдал" хэмээх утгын орны зарим онцлог Хураангуй: Монголчуудын өнө эртнээс нааш эрхэлсээр ирсэн нүүдлийн аж ахуй нь байнгын хөдөлгөөнтэй, сэтгэл хөдлөлтэй, өөр өөрийн ааш авиртай амьд объект болсон мал амьтантай харьцдаг; тэдгээрийн зүс, гадаад төрх нь улирал, байгаль цаг уурын онцлогоос шалтгаалж хувирч өөрчлөгддөг; тэднийг эрэх хайх, зүслэх шаардлага зайлшгүй урган гардаг учраас нүүдэлчдээс ажигч гярхай чанарыг зүй ёсоор шаарддаг. Иймээс нүүдэлчид өөрийн хотны хэдэн арваас эхлээд хэдэн зуун малыг өөр хооронд нь төдийгүй бусад айл, саахалтын малаас ялгахын тулд тэдний өнгө зүс, нас хүйс, авир араншин, явдал хөдөлгөөн зэрэг өвөрмөц шинжүүдийг ялган тогтоож малд нүдтэй болдог. Ийнхүү монголчууд нь хэдэн мянган жилийн турш нүүдлийн аж ахуй эрхлэх явцдаа мал маллах өвөрмөц арга ухаан, соёлыг цогцлоон хөгжүүлж, малынхаа тэрхүү нийтлэг болон өвөрмөц онцлог шинжийг нарийн танин мэдсэн мэдлэгээ монгол хэлэндээ шингээн хадгалсаар иржээ. Ингэж монгол хэлэнд нүүдлийн соёл, таван хошуу малтай холбоотой шаталсан шинжтэй олон арван утгын орон, тэдгээрийг бүрдүүлсэн үгийн сангийн баялаг нэрлэлтийг бий болгожээ. Эдгээрээс бид малын явдал, тэр дундаас “адууны явдал” гэсэн утгын оронд хамаарах нэрлэлтийг монгол ардын оньсого, зүйр цэцэн үгийн өнгөн бүтцээс хөөн судлахад монголчууд адууны үндсэн явдлыг ерөнхийд нь 11 ангилж, тэдгээрийг дотор нь 50 гаруй янзаар ялгаж, дүрслэн нэрлэжээ. Түлхүүр үгс: утгын орон, адууны явдал заасан үгс (алхах, шогших, хатирах, давхих гэх мэт)